2005
DOI: 10.1089/apc.2005.19.737
|View full text |Cite
|
Sign up to set email alerts
|

Preventing HIV Among Latino and African American Gay and Bisexual Men in a Context of HIV-Related Stigma, Discrimination, and Homophobia: Perspectives of Providers

Abstract: HIV-related stigma, discrimination, and homophobia impede community based efforts to combat HIV disease among Latino and African American gay and bisexual men. This commentary highlights ways to address these social biases in communities of color in Los Angeles from the perspectives of staff from HIV prevention programs. Information was collected from HIV prevention program staff participating in a two-day symposium. The outcomes from the symposium offer strategies for developing and implementing HIV preventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
141
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(144 citation statements)
references
References 35 publications
3
141
0
Order By: Relevance
“…20 HIV-related and gay-related stigma in Black and Latino communities is especially high, 9,21 making it important to develop solutions that reduce stigma and increase willingness to test for HIV infection. In high-risk populations including Black and Hispanic MSM, [9][10][11][12] we found that a significant majority of self-test users preferred to self-test versus test in a clinical setting. While the reason for testing preference was not determined in our study, we hypothesise that testing preference primarily relates to convenience and privacy issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 HIV-related and gay-related stigma in Black and Latino communities is especially high, 9,21 making it important to develop solutions that reduce stigma and increase willingness to test for HIV infection. In high-risk populations including Black and Hispanic MSM, [9][10][11][12] we found that a significant majority of self-test users preferred to self-test versus test in a clinical setting. While the reason for testing preference was not determined in our study, we hypothesise that testing preference primarily relates to convenience and privacy issues.…”
Section: Discussionmentioning
confidence: 99%
“…5 Engaging Black and Hispanic MSM in HIV testing has been challenging because of the high prevalence of HIV-related stigma and the limited utilisation of primary medical care. [9][10][11][12] HIV oral-fluid self-testing might reduce the stigma associated with seeking HIV testing, improve access to testing and prevention services and increase population-level serostatus awareness rates. 13 Although concerns about test kit affordability have been raised, HIV self-tests have been found to be acceptable in high-risk communities.…”
Section: Introductionmentioning
confidence: 99%
“…Recent discourse highlights the need for greater understanding of psychosocial factors that contribute to the spread of HIV within this disproportionately affected group of young men. 9,10 The current study focuses on stigma, which is one factor thought to be particularly salient to African American MSM infected with HIV. [9][10][11] Emerging research suggests that young MSM infected with HIV may experience multiple forms of stigma related to both their sexuality and seropositive status.…”
mentioning
confidence: 99%
“…9,10 The current study focuses on stigma, which is one factor thought to be particularly salient to African American MSM infected with HIV. [9][10][11] Emerging research suggests that young MSM infected with HIV may experience multiple forms of stigma related to both their sexuality and seropositive status. 12,13 HIV stigma may be particularly salient for young MSM who are African American, since research suggests that HIV-positive African Americans experience higher levels of HIV stigma than both Latinos and whites.…”
mentioning
confidence: 99%
See 1 more Smart Citation